The Effect of Local Complementary Feeding Based on Functional Foods on Improving the Nutritional Status of Stunted Children - Wahyuni, Nur (Journal Nutrizione, 2025)
Stunting is a serious public health problem in Indonesia, affecting children's growth and development, especially in the first 1000 days of life. Adequate complementary feeding of breastfeeding is very important to improve the nutritional status of children who are stunted. This study aims to evaluate the effect of MP-ASI administration based on local functional foods on the nutritional status of stunted children. This research was conducted with a quasi-experimental design in rural and urban areas with a high prevalence of stunting. A total of 120 stunted children aged 6–24 months were randomly divided into two groups, namely the intervention group given MP-ASI based on local functional foods (tempeh, moringa leaves, and mung beans), and the control group given standard MP-ASI. Nutritional status was measured using Z-scores for weight by age (BB/U), height by age (TB/U), and body weight by height (BB/TB) before, after 1 month, and after 3 months of intervention. The results showed that the intervention group experienced significant improvements in nutritional status, with a greater increase in BB/U Z-score compared to the control group. The intervention group showed an average improvement in Z-score from -2.1 to -1.1 after 3 months, while the control group showed only a small improvement from -2.0 to -1.8. These findings show the effectiveness of MP-ASI based on local functional foods in improving the nutritional status of stunted children. In conclusion, this study shows that the provision of MP-ASI based on local functional foods can significantly improve the nutritional status of stunted children. This approach can be an effective strategy to address stunting, especially in resource-constrained areas, and provide valuable insights for the development of nutrition interventions in similar contexts